THE INFLUENCE OF DRYING METHODS ON FLAVONOID CONTENT, WATER CONTENT, AND PREFERENCE LEVELS IN KERSEN LEAF TEA - Nisa, Wiva Varihatun; Yuswati; Ika Amalina Bonita (NUTRITURE JOURNAL, 2025)
Type II diabetes was caused by insulin resistance, meaning insulin was sufficient but blood sugar levels were not well controlled. Kersen leaves became one of the non-pharmacological treatments for type 2 diabetes because they contained flavonoid compounds that potentially acted as antidiabetic agents. The utilization of medicinal plants into products became the latest health innovation, namely herbal tea products. The drying process was required in herbal tea to reduce moisture content. Drying also had an impact on the total flavonoids of the herbal tea. This research aimed to determine the effect of drying methods on flavonoid content, moisture content, and preference level of kersen leaf tea (Muntingia calabura L.). The research method used a laboratory approach with two replications, using a Randomized Block Design (RBD) with three levels of treatment: P1 (direct sunlight), P2 (cabinet oven drying at 50°C), and P3 (cabinet drying at 60°C). Flavonoid testing used a UV-Vis spectrophotometer, moisture content used the gravimetric method, while preference level was assessed using a hedonic test. The average flavonoid content values were P1 (22 mg QE/g), P2 (44 mg QE/g), and P3 (33 mg QE/g). The average moisture content values were P1 (10.5%), P2 (5.11%), and P3 (5.01%). The ANOVA test results showed that the drying method significantly affected (p=0.001) the flavonoid content and did not significantly affect (p=0.0102) the moisture content and panelists’ preferences for taste, aroma, or color. The best treatment was found in P1, which produced kersen leaf tea with the best quality in terms of flavonoid content, moisture content, and preferred taste (distinct kersen leaf taste) and color (yellowish brown), while the preferred aroma (distinct kersen leaf aroma) was also found in P1.